New in development of negative hydrogen ion source with combined discharge - Dobrovolsky, A.; Goretskii, V.; Bazhenov, V. (Вопросы атомной науки и техники, 2016)
The presented work shows a progress in development of the cesiated negative hydrogen ion source with combined discharge. The dependence of Hion beam current on power introduced into the discharge is shown to have a saturation, which enables optimization of the power value. As well, nonlinear behavior is exhibited by the dependence of the beam current on anode hole size. One more essential parameter is the accompanying working gas flow from the source anode to the chamber. Further optimization of extracting system design and method of working gas supply can provide additional improvement of operation characteristics of the source.